2020
DOI: 10.1016/j.redox.2019.101373
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory cytokines IL-35 and IL-10 block atherogenic lysophosphatidylcholine-induced, mitochondrial ROS-mediated innate immune activation, but spare innate immune memory signature in endothelial cells

Abstract: It has been shown that anti-inflammatory cytokines interleukin-35 (IL-35) and IL-10 could inhibit acute endothelial cell (EC) activation, however, it remains unknown if and by what pathways IL-35 and IL-10 could block atherogenic lipid lysophosphatidylcholine (LPC)-induced sustained EC activation; and if mitochondrial reactive oxygen species (mtROS) can differentiate mediation of EC activation from trained immunity (innate immune memory). Using RNA sequencing analyses, biochemical assays, as well as database m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 60 publications
(81 reference statements)
5
70
0
Order By: Relevance
“…However, mitochondrial oxidants can induce phosphorylation of vascular endothelial growth factor receptor 2 (VEGFR2), resulting in activation of the receptor and subsequent angiogenesis. Similar to those findings, our previous reports showed that i) IL-35 inhibits lipopolysaccharide (LPS) and proatherogenic lipids LPC induced HAEC activation ( 5 , 7 ); ii) IL-35 suppresses vascular inflammation and atherosclerosis via inhibiting mitochondrial ROS( 8 , 9 , 34 – 37 ); iii) hypoxia may induce thrombus leukocyte transdifferentiation by upregulating endothelial cell-specific angiogenic markers ( 38 ); and iv) inhibition of caspase-1/inflammasome activation in EC improves ischemia-triggered angiogenesis ( 39 , 40 ). However, the question remained whether IL-35 modulates ischemia-triggered angiogenesis potentially via a ROS-related mechanism.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…However, mitochondrial oxidants can induce phosphorylation of vascular endothelial growth factor receptor 2 (VEGFR2), resulting in activation of the receptor and subsequent angiogenesis. Similar to those findings, our previous reports showed that i) IL-35 inhibits lipopolysaccharide (LPS) and proatherogenic lipids LPC induced HAEC activation ( 5 , 7 ); ii) IL-35 suppresses vascular inflammation and atherosclerosis via inhibiting mitochondrial ROS( 8 , 9 , 34 – 37 ); iii) hypoxia may induce thrombus leukocyte transdifferentiation by upregulating endothelial cell-specific angiogenic markers ( 38 ); and iv) inhibition of caspase-1/inflammasome activation in EC improves ischemia-triggered angiogenesis ( 39 , 40 ). However, the question remained whether IL-35 modulates ischemia-triggered angiogenesis potentially via a ROS-related mechanism.…”
Section: Introductionsupporting
confidence: 86%
“…We reported that IL-35 is a new responsive heterodimeric anti-inflammatory cytokine ( 4 ). IL-35 belongs to the IL-12 cytokine family and is potent in inhibiting various inflammatory diseases including lipopolysaccharide (LPS)-induced lung inflammation, human aortic endothelial cell (HAEC) activation ( 5 ), atherogenic lipids lysophosphatidylcholine (LPC) ( 6 – 8 ) -induced HAEC activation and atherosclerosis ( 9 ) but sparing innate immune memory (trained immunity) in HAEC ( 8 , 10 – 12 ) as we reported. IL-35 α -chain p35 (encoded by IL12A) is shared with IL-12; and ÎČ -chain EBI3 (encoded by Epstein–Barr virus-induced 3, EBI3) is shared with IL-27 and IL-39.…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…IL-35 protected against acute liver and kidney injury caused by LPS through inhibiting inflammatory responses (27,28). IL-35 also inhibited lysophosphatidylcholine-induced mitochondrial reactive oxygen species (mtROS) production and human aortic endothelial activation (29,30). Furthermore, IL-35 was reported to exert anti-apoptotic effects that prevent diabetic neuropathic pain and doxorubicin-induced cardiac injury (24,31).…”
Section: Discussionmentioning
confidence: 99%